2020
DOI: 10.2147/dmso.s238153
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predicting Metabolic Syndrome by Visceral Adiposity Index, Body Roundness Index and a Body Shape Index in Adults: A Cross-Sectional Study from the Iranian RaNCD Cohort Data</p>

Abstract: Background: The use of anthropometric indices is one of the new and low-cost diagnostic methods of metabolic syndrome (MetS). The present study aimed to determine optimal cutoff points for the visceral adiposity index (VAI), body roundness index (BRI), and a body shape index (ABSI) in the prediction of MetS. Methods: This cross-sectional study was performed on 10,000 individuals aged from 35 to 65 years, recruited in Ravansar Non-Communicable Diseases (RaNCD) cohort study, in the west region of Iran, in 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 38 publications
3
47
0
4
Order By: Relevance
“…In the present study, VAI and TyG index exhibited greater AUCs in identifying MetS than other traditional obesity-related parameters. The cutoff values of VAI to predict MetS were 1.74 in men and 1.83 in women in our study, compared to 4.1 and 4.2 in men and women, respectively, in an Iranian population [ 19 ], and 2.0 in middle-aged and elderly Chinese populations [ 40 ]. The difference between our study and the work by Baveicy et al [ 19 ] may be due to dietary and ethnic differences, as our results were closer to those of the reported Chinese populations [ 40 ].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In the present study, VAI and TyG index exhibited greater AUCs in identifying MetS than other traditional obesity-related parameters. The cutoff values of VAI to predict MetS were 1.74 in men and 1.83 in women in our study, compared to 4.1 and 4.2 in men and women, respectively, in an Iranian population [ 19 ], and 2.0 in middle-aged and elderly Chinese populations [ 40 ]. The difference between our study and the work by Baveicy et al [ 19 ] may be due to dietary and ethnic differences, as our results were closer to those of the reported Chinese populations [ 40 ].…”
Section: Discussionmentioning
confidence: 59%
“…A recent systematic review indicated that VAI was a practical predictor for type 2 DM in Asian populations [ 32 ]. Moreover, in a study of 10.000 Iranian individuals aged from 35 to 65 years, Baveicy et al found that VAI had a better predictive value for MetS than BRI and ABSI [ 19 ]. There are several possible reasons to explain why VAI outperforms the other obesity-related indices in predicting MetS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all the novel anthropometric markers, however, performed well in estimating elevated ASCVD risk. In Asian populations, ABSI failed to predict metabolic syndrome [ 49 , 50 ]. For identifying cardiovascular disease, ABSI seemed not to be a suitable predictor [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis study (2019) showed that VAI can be an independent predictor to T2DM in Asian populations [21]. Several studies have examined the predictive power of VAI using ROC curve analysis, the results of these studies agree on the accuracy and reliability of VAI for predicting T2DM, hypertension, and MetS [9,11,22]. Similar to some studies, in our study, this association was also established in CVDs risk factors; our ndings showed participants with higher VAI had signi cantly more hypertension, dyslipidemia, anthropometric indices (BMI, WHR, WC, BF and BFM) and lipid pro les compared to those with low VAI.…”
Section: Discussionmentioning
confidence: 96%